Development and Application of Synthetic Methods for the Production of Small Molecule Libraries - Leckett, Kyle (My University, 2016)
The synthesis of chemical libraries is a fundamental tool used to identify molecules with desirable biological activity. Recent developments in combinatorial synthesis techniques have allowed for the rapid generation of very large and diverse chemical libraries that can be used in conjunction with high-throughput screening (HTS) technology to identify lead molecules that can be potentially developed into pharmaceuticals. Libraries based around an oxindole scaffold (previously identified as inhibitors of cRAf1 kinase) were recently shown to display inhibitory effects against aminoglycoside phosphotransferases (APH) enzymes found in bacteria responsible for antibiotic resistance to aminoglycosides. Additionally, substituted quinazolines (similar in structure to the known drug Lapatinib) were identified as a potent inhibitor of both APH(2”)Id and ANT(2”). The present thesis involves the development of synthetic protocols suitable for the generation and subsequent biotesting of chemical libraries based around these hits in order to determine the pharmacophore in each case.
Keywords: Kyle Leckett